2016
DOI: 10.5897/ajb2016.15674
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of foot and mouth disease, bluetongue and pest de petites ruminants in Algeria: Historical perspective, diagnosis and control

Abstract: Molecular tools have become an increasingly important part of studying the epidemiology of infectious agents. These tools have allowed the aetiological agent within a population to be diagnosed rapidly with a greater degree of efficiency and accuracy than conventional diagnostic tools. They have enhanced understanding into the pathogenicity and virulence of the aetiological agent and subsequent deployment of appropriate control strategies. This paper reviews the contribution of molecular epidemiology to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…BTV infection is widespread in different countries worldwide with variable seroprevalence rates, including Eastern Sudan (91.2%) 26 , Grenada (78.4%) 27 , Brazil (64.81%) 28 , southwestern Ethiopia (30.6%) 29 , Italy (19%) 30 , Kosovo (11.6%) 31 , Algeria (16.44%) 32 , and China (6.79%) 33 . Likewise, different RT-PCR studies revealed BTV viropositivity of 72.88% in Kosovo 31 , 33.6% in Zambia 34 , and 20.61% in India 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BTV infection is widespread in different countries worldwide with variable seroprevalence rates, including Eastern Sudan (91.2%) 26 , Grenada (78.4%) 27 , Brazil (64.81%) 28 , southwestern Ethiopia (30.6%) 29 , Italy (19%) 30 , Kosovo (11.6%) 31 , Algeria (16.44%) 32 , and China (6.79%) 33 . Likewise, different RT-PCR studies revealed BTV viropositivity of 72.88% in Kosovo 31 , 33.6% in Zambia 34 , and 20.61% in India 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be assigned to the breeding systems adopted and the spatial and climatic features of each region surveyed each year (given that, as mentioned before, different regions were investigated over the four years). BTV infection is widespread in different countries worldwide with variable seroprevalence rates, including Eastern Sudan (91.2%) 26 , Grenada (78.4%) 27 , Brazil (64.81%) 28 , southwestern Ethiopia (30.6%) 29 , Italy (19%) 30 , Kosovo (11.6%) 31 , Algeria (16.44%) 32 , and China (6.79%) 33 . Likewise, different RT-PCR studies revealed BTV viropositivity of 72.88% in Kosovo 31 , 33.6% in Zambia 34 , and 20.61% in India 35 .…”
Section: Discussionmentioning
confidence: 99%
“…FMD is considered an endemic disease in specific regions worldwide, affecting extensive areas of Africa, Asia, and South America. The geographical distribution of each FMD serotype varies, with serotype O having the widest spread [14,15]. Direct losses caused by FMD, such as reduced milk and meat production, and indirect losses significantly impact the food security and livelihoods of communities in low-income areas where FMD is prevalent [3,13,16,17].…”
Section: Introductionmentioning
confidence: 99%